Pleural procedural complications: prevention and management - Corcoran, John P.; Psallidas, Ioannis; Wrightson, John M.; Hallifax, Robert J.; Rahman, Najib M. (Journal of Thoracic Disease, 2015)
Pleural disease is common with a rising case frequency. Many of these patients will be symptomatic and require diagnostic and/or therapeutic procedures. Patients with pleural disease present to a number of different medical specialties, and an equally broad range of clinicians are therefore required to have practical knowledge of these procedures. There is often underestimation of the morbidity and mortality associated with pleural interventions, even those regarded as being relatively straightforward, with potentially significant implications for processes relating to patient safety and informed consent. The advent of thoracic ultrasound (TUS) has had a major influence on patient safety and the number of physicians with the necessary skill set to perform pleural procedures. As the variety and complexity of pleural interventions increases, there is increasing recognition that early specialist input can reduce the risk of complications and number of procedures a patient requires. This review looks at the means by which complications of pleural procedures arise, along with how they can be managed or ideally prevented.